Vpr Enhances HIV-1 Env Processing and Virion Infectivity in Macrophages by Modulating TET2-Dependent IFITM3 Expression - Qi Wang (American Society for Microbiology, 2019)
ABSTRACT HIV-1 Vpr enhances viral replication in human macrophages via multiple mechanisms that are not clearly defined. It does not affect HIV-1 virion production during the first round of infection. We have recently discovered that Vpr targets the DNA demethylase TET2 for degradation, which leads to sustained interleukin-6 (IL-6) expression and elevated HIV-1 replication. We report here that Vpr enhanced Env processing in infected macrophages, associated with increased Env incorporation into virions with higher infectivity. Interestingly, IFITM3 was constitutively expressed in macrophages in a TET2-dependent fashion. We showed that Vpr-enhanced Env processing depended genetically on TET2 and IFITM3. We further showed that Vpr reduced IFITM3 expression by reducing demethylation of the IFITM3 promoter in macrophages, associated with degradation of TET2 and reduced TET2 binding to the IFITIM3 promoter. Our findings indicate that the Vpr-TET2 axis enhances HIV-1 replication in macrophages via two independent mechanisms: reduced IFTIM3 expression to enhance Env processing and virion infectivity and sustained IL-6 expression to increase HIV-1 replication. The Vpr-TET2 axis may provide a novel target to develop therapeutics to inhibit HIV-1 infection and pathogenesis. IMPORTANCE How Vpr enhances HIV-1 replication in macrophages is still unclear. We report here that Vpr enhanced HIV-1 Env processing during the first round of HIV-1 replication, resulting in virions with higher Env incorporation and viral infectivity. These higher-quality viral particles contributed to elevated infection during the second round and spreading infection in macrophages and other HIV-1 target cells. We have recently discovered that TET2 is a novel host factor degraded by Vpr, which leads to sustained IL-6 expression in macrophages. Interestingly, Vpr-enhanced HIV-1 Env processing depended on both the IFITIM3 and TET2 genes. The constitutive expression of IFITIM3 expression in macrophages was maintained by TET2, which demethylated the IFITIM3 promoter. We conclude that the Vpr degrades TET2 to enhance HIV-1 replication in macrophages by reducing IFITIM3 expression to increase viral Env processing, virion incorporation, and infectivity and by sustaining IL-6 expression to increase HIV-1 gene expression. The Vpr-TET2 axis may serve as a novel target to develop anti-HIV drugs to inhibit HIV-1 infection and pathogenesis.